KONSEP PENDIDIKAN ISLAM PERSPEKTIF MAHMUD YUNUS - Bunyamin, Bunyamin (Universitas Muhammadiyah Prof Dr Hamka, 2019)
The condition of Islamic education in Indonesia has existed since the Dutch colonial period, especially Islamic education is in a very dwarf condition that is not yet able to contribute to the progress of the nation. This happens due to the narrow mindset of the community in interpreting the verses of the Qur'an. In addition, there is discrimination by the colonialists against Islamic education. Education established by new Muslims around Islamic boarding schools which are considered unable to meet the demands of the times. This research focuses on the concept of Islamic education according to Mahmud Yunus by using qualitative research, content analysis approaches that examine historical, textual, and comparative approaches. Findings from the results of this study according to Mahmud Yunus, education is more specialized in moral education than the objectives of Islamic education, in the process of learning that places priority over methods. Thus the researcher is able to conclude about the concept of Islamic education from Mahmud Yunus from the objectives, methods, institutions, systems, and curriculum that really gives a great influence on Islamic education in Indonesia.